Frontispiece: A Membrane‐Free Redox Flow Battery with Two Immiscible Redox Electrolytes. Issue 41 (27th September 2017) - Navalpotro, Paula; Palma, Jesus; Anderson, Marc; Marcilla, Rebeca
Abstract : Batteries The use of immiscible electrolytes would make the removal of membranes from batteries possible. In their Communication on page 12460 ff. R. Marcilla and co‐workers demonstrate such a "proof‐of‐concept" battery.